Monetary policy transmission in Nigeria: Assessing the effectiveness of the bank lending channel - Yusuf D. Bulus; George Okorie; Kayode E. Adedeji (West African Journal of Monetary and Economic Integration, 2024)
The paper examines the connection between monetary policy transmission and bank lending in Nigeria. It estimates a quarterly data set covering from 2000 to 2022 while adopting the Autoregressive Distributive Lag (ARDL) approach after the variables' stationarity exhibited a mixture of I(0) and I(1). The results show very strong evidence of a cointegrating relationship between the lending ability of banks, as represented by credit to the private sector and the monetary policy transmission process as proxied by the Monetary Policy Rate (MPR) and Money Supply (M2). We also found that the monetary policy transmission in Nigeria via the bank lending channel exists, though weak. The coefficient of the error correction term (ECT) is negative and significant in accordance with the error correction principle. The speed of adjustment, given the initial shock in credit to the private sector, is corrected to the tune of about 33 percent per quarter. The outcome implies that credit to the private sector performs a key function in the process of monetary policy transmission through the flexibility of lending channels. This study, therefore, reemphasises the importance of safeguarding banking system stability for an efficient implementation of monetary policy in Nigeria.
Keywords: E51; E52; G21; 330; Banks; Lending Channel; Monetary Policy; Transmission Mechanisms; ARDL